SYNERGY EFFECT: HOW TO CAPTURE VALUE IN THE BUSINESS STRATEGY? A CASE OF IT BUSINESSES IN NORTH MACEDONIA - Snezhana HRISTOVA; Ivona MILEVA; Elena BUNDALESKA (Studia Universitatis Babeş-Bolyai Negotia, 2022)
Nowadays, businesses are required to create added value and difference. In recent years, the synergy perspective grew into one of the main concerns of corporate and strategic management. It creates a new path for change in the way of designing the business strategy, characterized by the collaboration mindset embedded in the overall strategic thinking context. This paper investigates the perceptions and practices of the IT managers with regards to the potential of synergy strategies. It aims to explore the growing importance of synergies between all elements, stakeholders, and processes in the organization, with a particular emphasis on the connections which include cooperation, interaction and working together to realize accepted purposes and strategic goals. The primary data were obtained through a survey carried out in the IT businesses in North Macedonia and evaluated by using the descriptive statistics. The key findings indicate that synergy strategies can create added value on the company’s sustained competitive advantage. The results showed that the synergy strategy appears to be a good managerial practice to be fostered on the organizational level to produce greater results. As the synergy effects seem to be a widespread practice, but rarely discussed topic within the IT sector in North Macedonia, the research will attempt to provide a theoretical contribution to the academic community, but also to help local managers to identify and coordinate opportunities for integrating the sinergy in their business strategy. Apart from the main research focus, our aim expands further to making a broader contribution to the theories of strategy and organization.